Implicit Expression of the 2014 World Cup Football's News: A Pragmatic Analysis: (Ungkapan Implisit dalam Berita Bola Sepak Piala Dunia 2014: Analisis Pragmatik) (Jurnal Bahasa, 2014)
This research explores the implicit meaning of the sports news of the 2014 FIFA World Cup Championship as published on websites. Data taken from inserted sentences in online news is analysed to reveal the intended meanings in light of the relevance theory developed by Sperber and Wilson (1986), which emphasizes the concept of context, context effects and processing effort. The study found that many events can be made known through an implicit expression after pragmatic interpretation. The implicit expressions in sports news also do not pose a problem for the reader to obtain the intended meaning which is rich in contextual information.Keywords: implicit expression, FIFA World Cup 2014, pragmatics, relevance theory